Individual and community-level determinants of knowledge of obstetric danger signs among women in Southern Ethiopia: A multi-level mixed effect negative binomial analysis - Amanuel Yoseph; Yilkal Simachew; Berhan Tsegaye; Asfaw Borsamo; Yohans Seifu; Mehretu Belayneh (PLoS ONE, 2025)
Introduction One of the key strategies to achieve the sustainable development goal by reducing maternal deaths below 70 per 100,000 is improving knowledge of obstetric danger signs (ODS). However, mothers’ knowledge of ODS is low in general and very low in rural settings, regardless of local and national efforts in Ethiopia. Further, there is significant variation of ODS knowledge among women from region to region and urban/rural settings. Most studies are limited only to northern Ethiopia and focused on individual-level determinants. Thus, this study aimed to assess the individual and community-level determinants of knowledge of obstetrics danger signs among women who delivered in the last 12 months in the northern zone of the Sidama region, Ethiopia. Methods We conducted a community-based cross-sectional study from October 21 to November 11, 2022. A multi-stage sampling procedure was utilized to select study participants. A structured and pretested questionnaire was utilized to collect data. Open Data Kit (ODK) smartphone application was used to collect data at women’s homes. A multi-level mixed-effects negative binomial regression model was used to control effects of clusters and confounders. Results The overall response rate of this study was 99.12%. The proportion of knowledge of obstetrics danger sign was 22.3% (95% CI: 18.7, 25.9). Government-employed women [adjusted incidence ratio (AIR) = 1.37; 95% CI: 1.20, 1.56], women who had exposure to mass media (AIR = 1.16; 95% CI: 1.08, 1.25), women who had received model family training (AIR = 1.15; 95% CI: 1.10, 1.25), autonomous women (AIR = 1.34; 95% CI: 1.25, 1.46), women who had faced health problems during pregnancy (AIR = 1.21; 95% CI: 1.11, 1.32), and urban women (AIR = 1.22; 95% CI: 1.09, 1.62) were determinants positively affect knowledge of ODS. Conclusion Only one in five women has good knowledge of ODS in the study setting. Urban residence, mass media exposure, receiving model family training, facing health problems during pregnancy, and women’s autonomy were the main determinants of knowledge of ODS. Any intervention strategies should focus on multi-sectorial collaboration to address determinants of knowledge of ODS at the individual and community level. Reinforcing the existing model family training, particularly focusing on rural women and women who denied autonomy in decision-making about health care, should be considered. Awareness creation should be increased about ODS through mass media exposure.